The Role of Pragmatics in Improving English Listening and Speaking Skills - Dea Saharani; Siregar, Huda Hizkia Ahmad; Hasibuan, Syafira Hasan; Dalimunthe, Alya Fadhillah; Siregar, Deasy Yunita (Universitas Negeri Medan, 2025)
Pragmatics is the study of how we make sense of what others say when we talk. Meaning links our words with our body language. It can change depending on the circumstance, the relationship between the individuals, and other social variables. Its quick growth has made English a worldwide language that brings people together. English is a language that many people from different places and cultures can speak. In everyday life, people use English in many different situations and talk in many different ways. Speakers need to know about different aspects of pragmatics to avoid misunderstandings when they talk and listen. Using English in fun and interesting ways can help everyone, especially those learning it as a second language, get better at talking and writing. Thomas describes